(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract. This article explores the Grammar-Translation Method (GTM) and Communicative Language Teaching (CLT) as two widely used approaches in English as a Foreign Language (EFL) education. GTM focuses on grammar rules and translation, whereas CLT emphasizes communication and interaction. Each method has its advantages and limitations, making them suitable for different learning goals. While GTM is effective for developing grammar accuracy and reading comprehension, CLT enhances speaking fluency and listening skills. This article discusses their key principles, strengths, and weaknesses, providing insights into their application in modern EFL classrooms.